2014
DOI: 10.1037/a0036659
|View full text |Cite
|
Sign up to set email alerts
|

Within-person analyses of situational interest and boredom: Interactions between task-specific perceptions and achievement goals.

Abstract: Despite the increasing number of studies examining the correlates of interest and boredom, surprisingly little research has focused on within-person fluctuations in these emotions, making it difficult to describe their situational nature. To address this gap in the literature, this study conducted repeated measurements (12 times) on a sample of 158 undergraduate students using a variety of self-report assessments and examined the within-person relationships between task-specific perceptions (expectancy, utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 95 publications
6
83
0
Order By: Relevance
“…Lacking historical positionality beyond the marginalized or the victim, non-White students are more likely to look upon such a narrative with skepticism and dissonance (Chikkatur, 2013;Epstein, 2009;VanSledright, 1998). Consequently, they find learning history/social studies boring, inversely affecting their motivation to learn historical material (Stodolsky, Salk, & Glaessner, 1991;Tanaka & Murayama, 2014). Importantly, race and class should not be conflated.…”
Section: Acknowledging the History Content Knowledge Achievement Gapmentioning
confidence: 99%
“…Lacking historical positionality beyond the marginalized or the victim, non-White students are more likely to look upon such a narrative with skepticism and dissonance (Chikkatur, 2013;Epstein, 2009;VanSledright, 1998). Consequently, they find learning history/social studies boring, inversely affecting their motivation to learn historical material (Stodolsky, Salk, & Glaessner, 1991;Tanaka & Murayama, 2014). Importantly, race and class should not be conflated.…”
Section: Acknowledging the History Content Knowledge Achievement Gapmentioning
confidence: 99%
“…Teachers' enthusiasm for teaching was thought of as an important part of professional competence of teachers (Kunter et al, 2013). According to this, enthusiastic teachers may facilitate their students' interest and dampen their boredom in lectures (Kim and Schallert (2014); Tanaka and Murayama, 2014). Based on the controlvalue theory of achievement emotions (Pekrun, 2006;Pekrun et al, 2007), the current study examined relationship between perceived teacher enthusiasm and class-related boredom during theoretical lesson hours among Chinese nursing students.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, Frenzel et al (2009) and Kim and Schallert (2014) found that perceived teacher enthusiasm can predict learning enjoyment and interest in students. Additionally, interest in learning was found to set significant precedents for boredom experienced by students (Daschmann et al, 2014), and interests in specific tasks were found to be negatively correlated with boredom (Tanaka and Murayama, 2014). Based on the separated, reciprocally related yet not mutually exclusive relationship between positive and negative emotions (Cacioppo and Berntson, 1994;Schimmack, 2001;Smith et al, 2006;Schimmack and Colcombe, 2007), perceived teacher enthusiasm may induce situational interest and reduce class-related boredom.…”
Section: The Dampening Effects Of Perceived Teacher Enthusiasm On Clamentioning
confidence: 95%
See 1 more Smart Citation
“…Educational studies have discovered negative correlations between the perceived task difficulty and level of interest [29,30]. It follows that female participants, who reported having significantly more difficulty with the biomimicry exercise, may have been less interested by it.…”
Section: Discussionmentioning
confidence: 99%